A demographic profile of patients seeking MTP for gross congenital malformations in a tertiary referral hospital in North India - Jain, Shaveta; Rani, Vandana; Sangwan, Roopa; Jain, Nitin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of the study was to study the sociodemographic, obstetrics profile and folic acid intake in women seeking medical termination of pregnancy for gross congenital malformed fetus (GCMF)and to study pattern of GCMF. Methods: A cross sectional study was conducted among women who underwent medical termination of pregnancy for congenital malformation in fetus in tertiary referral hospital of north India. The details regarding their sociodemographic profile, previous obstetrics history, pattern of GCMF, history of folic acid intake and method of termination were taken. Results: 61% of women seeking medical termination of pregnancy for GCMF were of age group 20-25 years. 75 women were from rural area which is 83.3 % in present study. Only 13.3 % of women in present study were illiterate. Most of the women 66.6 % belongs to middle class of society in present study. 40 % women seeking medical termination of pregnancy for congenital anomaly were primigravida. 96.6 % of patient’s congenital anomaly was detected in second trimester. 74.4 % of patient had central nervous system (CNS) congenital anomaly, most common was anencephaly in 34 patients followed by meningocele/myelomeningoceles in 9 fetuses. Only 27 % women had history of folic acid intake and 55 patients were given mifepristone 200 mg with 400 mcg misoprostol while 32 patients who had previous history of cesarean section were given lower doses. Conclusions: Anencephaly was the most common congenital anomaly detected. The high reporting of anencephaly suggests the need for a fortification of folic acid in food. Dismal rate of cardiac malformation suggests there is need of inclusion of cardiac echo in level II anomaly scan. Prolonged induction to abortion time in present study shows need of further studies for simultaneous or 24-hour regimen of mifepristone and misoprostol and higher doses of misoprostol.